Organic matter from the Chicxulub crater exacerbated the K-Pg impact winter - Lyons, S.L.; Karp, A.T.; Bralower, T.J.; Grice, Kliti; Schaefer, Bettina; Gulick, S.P.S.; Morgan, J.V.; Freeman, K.H. (NATL ACAD SCIENCES, 2020)
An asteroid impact in the Yucatán Peninsula set off a sequence of events that led to the Cretaceous-Paleogene (K-Pg) mass extinction of 76% species, including the nonavian dinosaurs. The impact hit a carbonate platform and released sulfate aerosols and dust into Earth's upper atmosphere, which cooled and darkened the planet - a scenario known as an impact winter. Organic burn markers are observed in K-Pg boundary records globally, but their source is debated. If some were derived from sedimentary carbon, and not solely wildfires, it implies soot from the target rock also contributed to the impact winter. Characteristics of polycyclic aromatic hydrocarbons (PAHs) in the Chicxulub crater sediments and at two deep ocean sites indicate a fossil carbon source that experienced rapid heating, consistent with organic matter ejected during the formation of the crater. Furthermore, PAH size distributions proximal and distal to the crater indicate the ejected carbon was dispersed globally by atmospheric processes. Molecular and charcoal evidence indicates wildfires were also present but more delayed and protracted and likely played a less acute role in biotic extinctions than previously suggested. Based on stratigraphy near the crater, between 7.5 × 1014and 2.5 × 1015g of black carbon was released from the target and ejected into the atmosphere, where it circulated the globe within a few hours. This carbon, together with sulfate aerosols and dust, initiated an impact winter and global darkening that curtailed photosynthesis and is widely considered to have caused the K-Pg mass extinction.